Dividend policy : a business perspective - Trung Tran, Quoc (Emerald Publishing Limited, 2024)
Dividend Policy: A Business Perspective explores the critical role of the business environment in shaping corporate decisions, with a specific focus on dividend policy. A typical business environment commonly has three levels: The first level, the internal environment, encompasses all factors within the firm's control. This includes corporate operations, resources, and the interests of internal stakeholders, including shareholders, the board of directors, the CEO, and employees. The second level is the industry environment or micro-environment, involving external individuals and organizations tied to the firm's operations. The third level, the macro-environment, comprises external and general conditions affecting all firms in the economy. Each level, significantly impact dividend decisions in their own unique way. Here, the PESTEL model is employed to analyse six key factors: Political, Economic, Social, Technological, Environmental, and Legal. Author Quoc Trung Tran delves into the impact of these factors on dividend policy, focusing particularly on the role of technological factors, where theoretical mechanisms and empirical evidence are currently lacking. Written with a finance and treasury readership in mind, this work will appeal to students, educators, researchers, managers, and policymakers alike.